Study on the Dynamics of Cortisol Secretions in Hypertensive Elderly Patients - Doina Carstea; Diana-Maria Trasca; A. P. Carstea; E. T. Trasca (International Journal of Hypertension)
Ageing is defined as a slow, irreversible process of cellular changes, that are due to a lack of balance between degradation and repair, a continuous interaction between physiological and pathological processes. Physiological aspects in elderly people are often confused with disease. Given these general considerations, we would make observations about the dynamics of cortisol secretion in healthy elderly subjects and patients with a diagnosed cardiovascular disease, more precisely hypertension. The study was conducted during 2003–2010, on a number of 135 patients older than 65 years of age, who were divided into two groups: one group counting 66 patients and consisting of healthy elderly controls (without systemic disease, renal, endocrine, or cardiovascular known issues) and group 2 who consists of 69 elderly patients who associate known hypertensive and other cardiovascular issues.